THE PHENOMENON OF THRIFTING IN THE STUDY OF CITIZENSHIP ECONOMICS AT THE SAMBU MARKET IN MEDAN CITY - Nurul; Jamaludin (JURNAL SETIA PANCASILA, 2025)
The This study aims to examine the phenomenon of thrifting in the study of economic civic in the sambu market in Medan City. The phenomenon of thrifting as one of the economic trends that develops in society, especially in the context of community economics, is seen as an activity that has an impact on changes in economic and social behavior among urban communities. Using a phenomenological approach, this study highlights the views and experiences of thrifting sellers and buyers participating in the market. The qualitative method was chosen to provide an in-depth picture of how thrifting is seen as an economic activity that impacts consumption patterns, social awareness, and citizenship. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis was carried out using the Interpretative Phenomenological Analysis (IPA) approach, using ATLAS.ti software to simplify the analysis process and provide updates in this study. The findings of this study are expected to provide new insights in the study of economic civic, especially related to economic behavior in the context of civil society in the city of Medan. The results of the study show that thrifting in the sambu market is not only an economic activity, but also a space for social interaction that strengthens the solidarity of local communities. Thrifting actors build social relations based on trust, collaboration, and care, which reflects people's economic practices in the context of civil society. The practice of thrifting also encourages people to participate in inclusive and sustainable economic activities, despite the gap between government regulations and market activities that drive citizens' economies. The conclusion of this study reveals that the phenomenon of thrifting in the sambu market reflects the important role of community-based economic activities in building social awareness and strengthening the structure of civil society in the context of civic economic studies.